Profile of Serum Insulin-like Growth Factor-1 Levels in Patients with Acne Vulgaris - I G.A. Kencana Wulan; Afif Nurul Hidayati; Hari Sukanto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Acne vulgaris (AV) is a skin disease that is commonly found in adolescence. In addition to causing physical disorders, acne vulgaris affects the quality of life of patients that cause social disorder, psychological, and emotional. Based on the observations of the experts, AV is rarely found in non-westernized populations, indicates an underlying environmental factors including diet. Excessive sebum production has an important role in the pathogenesis of AV. One of the factors which allegedly associated with the production of sebum and diet is IGF-1 in serum. Purpose: To evaluate the levels of IGF-1 serum in patients with AV with varying degrees of severity. Methods: This study is an observational cross-sectional study in 38 AV patients aged 15-24 years at the Outpatient Clinic of Dermatovenereology Department of Dr. Soetomo Hospital Surabaya as many as 38 people. The severity of AV are grouped according to the method of Combined Acne Severity Classification (CASC). Anamnesis of diet based on the table of load and glycemic index foods. Subjects has been collected through consecutive sampling. Results: Serum IGF-1 levels in the mild AV group was 155,000 (SD±23,381) µg/ml, in the moderate AV group was 211,052 (SD±85,498) µg/ml and in severe AV group was 150,000 (SD±45,826) µg/ml. Serum IGF-1 levels in male group was higher than female, was 199,230 (SD±85,582) µg/ml and in female group was 174,000 (SD±58,238) µg/ml. Serum IGF-1 levels in the aged group of 15-20 years was 192,270 (SD±80,766) µg/ml, higher than the aged group of 21-24 years, was 169,380 (SD±46,829) µg/ml. Conclusion: The mean levels of IGF-1 in patients with moderate degrees of AV was higher than mild or severe. IGF-1 levels can vary influenced by many factors. Key words: acne vulgaris, serum IGF-1, severity degrees of acne vulgaris.